MSCar: Enhancing Message Sequence Charts with Interactivity for Analysing (Automotive) Communication Sequences - Sedlmair, Michael (Electronic Communications of the EASST, 2008)
Message Sequence Charts (MSCs) are a standardized and widespread form to visually describe interactions in distributed systems. Our approach proposes the enrichment of large scaled MSCs with novel interaction and design techniques used in the field of information visualization. Additionally, we show a graphical solution to visualize parallel, multi-directed communication processes in MSCs. Instead of the common application to specify system behaviours our interactive MSCs are aimed at exploring and diagnosing dependencies in network communication in general and, regarding our special requirements, within in-car communication traces. We implemented a prototype called MSCar with Focus and Context techniques, Dynamic Path Highlighting, Details on Demand and Colour Coding to support the users' cognitive abilities. A qualitative user study on MSCar gave uspreliminary feedback and disclosed potentials of our approach.